Frequency agile antenna integrated with band pass filter - Mohamad Dahlan, Ahmad Marwan (2013)
In the era of wireless communication, new problem arises when user’s attention increases together with new development of wireless applications. The limited frequency spectrum, which allows only one application to operate at the same time and frequency, has created resource issue for the wireless communication industry. Hence, new frequency agile technologies such as Software Define Radio and Cognitive Radio systems are being developed. One of the requirements of this type of application is an antenna system that is able to change its operating frequency as instructed by the back end system. This research explores the possibility of integrating band pass filters to manipulate the operating frequency of a broadband antenna. RF diode, inductors and capacitors are used as switching mechanism to actively change the operating frequency. Based on the spectrum allocation in Malaysia, frequency range from 1GHz to 6GHz was chosen due to the allocation of many types of communication applications such as mobile applications, unlicensed band and satellite communication. A proof of concept was done for active switching at 1.3GHz and 2GHz of the antenna prototype. Another structure was fabricated to implement frequency reconfigurability operation at 1.3GHz, 2GHz, 3GHz, 4GHz, 5GHz and 6GHz using copper strips instead of active elements. Simulated and measured results showed good agreement for 1.3GHz – 2GHz active switching prototype while 1.3GHz – 6GHz copper strip prototype shows minor shifts and degradation at high frequencies in measured result. From the data collected in this research, band pass filter integrated antenna shows high potential to be used as frequency agile antenna with active switching capability. The results from simulation and measurement of fabricated structures are analyzed and discussed in detail in this thesis. This research contributes to the development of frequency agile antenna design for future frequency agile application.